Laminin and its Related Peptides for the Treatment of Alzheimer's Disease - Monji, Akira; Tashiro, Ken-ichiro; Yoshida, Ichiro; Hashioka, Sadayuki; Kato, Takahiro; Kanba, Shigenobu (Current Medicinal Chemistry - Central Nervous System Agents, 2005)
Alzheimer's disease (AD) is one type of dementing central nervous amyloidosis characterized by two different types of fibrillar deposits, namely senile plaques and neurofibrillary tangles. Amyloid-β-proteins (Aβ) are the major constituents of senile plaques. The aggregation of soluble Aβ into insoluble amyloid fibrils is believed to be an important step in the pathogenesis of AD and the prevention of this process therefore seems to be a promising strategy for the treatment of AD. Laminin is an important extracellular matrix (ECM) protein which has been reported to accumulate in the senile plaques. It supports such biological activities as cell adhesion, cell proliferation, neurite outgrowth. Recent reports have revealed that laminin inhibits both Aβ fibril formation and Aβ neurotoxicity in vitro . Laminin-related peptides, which have almost the same biological activities as laminin, have also recently been reported to inhibit Aβ fibril formation and/or Ab neurotoxicity. Finally, Laminin can induce a complete disaggregation of Aβ amyloid fibrils by disassembly into protofibrils and subsequently into an amorphous aggregate. These results thus suggested that laminin or its related peptides may be useful as an effective therapeutic agent for the treatment of AD.
Keywords: Alzheimer' s disease